Pelestarian Tradisi Ngumbah Keris dan Peningkatan Ekonomi Masyarakat melalui Demonstrasi Ngumbah Keris pada Bulan Suro di Ponorogo - Musarofah, Siti (Proceedings of Annual Conference on Community Engagement, 2018)
The purpose of the ngumbah keris demonstration is to preserve the tradition of ngumbah keris in Suro month in Ponorogo so as not to become extinct, and to attract tourists to visit Ponorogo so as to improve the economy of the Ponorogo community. Based on the research and situation analysis, the following problems can be identified: 1) Some keris owners in Ponorogo never did the tradition of ngumbah keris because they did not know how, so that their keris became dirty, rusty and lost its beauty. 2) There is a keris owner who takes care of and kills his keris but the result is that the prestige of the keris is lost (does not appear) because of the way the keris is erroneous or wrongly chooses warangan, so he chooses to pay the author's services. 3) The existence of such inventor services, the economic value of the tradition of ngumbah keris can only be felt by the inventors, namely getting a reward for his services in bathing keris belonging to other people, in addition to the creators of Ponorogo people cannot feel an economic increase from this activity. 4) Before 2018 the tradition of chanting keris in Ponorogo was only carried out by certain individuals individually in their respective homes, so that many young people did not know about the tradition of hanging keris in Ponorogo. Based on these problems, the solution offered was to hold a demonstration to celebrate keris in the month of Suro which was included in the Grebeg Suro Ponorogo program.